Location indicators of automated external defibrillator electrode patches using image processing techniques. (February 2017) - Chen, Wen-Yuan; Huang, Shih-Yen; Wang, Mei; Cheng, Shih-Sung
Highlights: We developed a location indicator method for AED electrode patches. The body proportional positing method was used to solve the problem of different body shapes. We used the neck, shoulders, and slope features to accurately determine the AED electrode patch locations. The standard deviation was used to compensate the trained AED electrode patch. Abstract: A sudden cardiac arrest can lead to death if emergency treatment is unavailable. However, the proper use of an automated external defibrillator (AED) can save lives. This study is based on an image processing technology for automatically indicating the electrode patch locations of an AED. We use three strategies to achieve this goal: (1) Create a body proportional positing method (BPPM) to solve the problem of differing body shapes. (2) Apply three features: the center of the neck, the ends of the shoulder, and a calculation of the slope to accurately determine the correct electrode patch locations of the AED. Finally, (3) apply a standard deviation to compensate the calculated center points of the trained AED electrode patches. Simulation results demonstrate that our scheme is an effective and accurate method for indicating the locations of AED electrode patches. Graphical abstract: